(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents a new class of functions called contra-(τ_1,τ_2)p-continuous functions. Furthermore, several characterizations and some properties concerning contra-(τ_1,τ_2)p-continuous functions are considered.